Plant Conservation Based on Tri Mandala Concept on Homegarden at Pakraman Penge Village, Baru Village, Marga District, Tabanan Regency, Bali - I Dewa Putu Darma; Sutomo Sutomo; Siti Fatimah Hanum; Rajif Iryadi (Universitas Gadjah Mada, 2020)
Penge Pakraman village is a traditional village that has the potency to become ecotourism. The emergence of new tourist attractions affects land changes to support tourism activities. This causes the number of plant species in nature to decrease. Plant conservation by utilizing local wisdom is one effort to reduce the decrease of plant species number. The application of Tri Hita Karana and Tri Mandala in Balinese daily life able to support plant conservation activity. The objective of this research was to determine the role of Tri Mandala concept in plant conservation at Pakraman Penge home garden. Data collection methods are carried out through observation plant location with inventory number and name of plants in house sample. Plant use continues with study literature. The results of an inventory of plant diversity in home gardens of Pakraman Penge village recorded 70 species of plants from 16 houses sample. The plant habitus varied from herbs, shrubs until trees. Plant species in the home gardens have functions for ceremonies (51%), medicinal (24%), ornamental (17%), food (6%), and spices (2%). However, based on the location, most plant species were found in madya mandala and the lowest were found in utama mandala. We also found plants with conservation status consist of least concerned (15 species), vulnerable (Dracaena draco), near threatened (Cycas rumphii), endangered (Coffea arabica). Therefore, the application of Tri Mandala concept on Balinese home gardens supports plant conservation and gives economic benefit in individual level